Analisis Faktor Sosio-Demografi Terhadap Kemampuan Fungsional Activity Daily Living Pada Klien Stroke Iskemik di Blud RSUD dr. Doris Sylvanus Palangka Raya - Wijaya Atmaja Kasuma (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
The prevalence of stroke worldwide is 33 million, which is 16.9 people had stroke in 2010, causing 11.3% of deaths worldwide as second leading global cause of death under heart disease. In Central Kalimantan, prevalence of stroke based on diagnosis by health professionals is 0.53%. According to districts it ranges from 0.21% -1.58% and Palangka Raya City has a stroke prevalence of 0.85%. Stroke causes brain vascularization disorders, motor dysfunction that causes the patient limitations, thereby increasing the risk of complications. A person with movement disorders will have an impact on their daily activities. Aims of this study to determine the socio-demographic factors that affect the level of functional ability of clients in performing daily living activities (ADL) of ischemic stroke clients at dr. Doris Sylvanus Palangka Raya hospital. This study used a cross sectional study approach. This reresearch would see an overview of each variable to be studied using the Barthel index instrument and data from the socio-demographic respondents. The results showed that socio-demographic factors that significantly influence and influence the functional ability of client ADL are age and occupational variables, while other variables, namely gender, marital status and education, do not affect the ADL functional status of respondents.